Cost-effectiveness of adding a birth dose of hepatitis B vaccine in the Dafra district of the Hauts-Bassins Region in Burkina Faso (NéoVac Study). Issue 33 (30th July 2021) - Gosset, Andréa; Diallo, Mamadou Yaya; Betsem, Edouard; Schaeffer, Laura; Meda, Nicolas; Vray, Muriel; Sombie, Roger; Shimakawa, Yusuke; Boyer, Sylvie
Abstract: Background: The World Health Organization (WHO) recommends a first hepatitis B vaccine dose within 24 h of birth (HepB-BD) to prevent mother-to-child transmission. Evidence for this strategy's economic value in Africa is limited. We assessed the costs and cost-effectiveness of adding HepB-BD to the current three-dose pentavalent schedule (HepB3) in the Dafra district of the Hauts-Bassins Region in Burkina Faso. Methods: Using a decision tree combined with a Markov model, we estimated the expected number of life-years (LY) and disability-adjusted life-years (DALYs) saved, incremental costs, and incremental cost-effectiveness ratios (ICER) of HepB-BD + HepB3 versus HepB3 alone in Dafra's 2017 birth cohort (n = 11, 462). Institutional delivery rates, vaccine coverage, and vaccination costs from a health system perspective were estimated from field-collected data. We estimated the effectiveness of HepB-BD, age-specific transition probabilities, and horizontal transmission risks using data from previous African studies. Costs and health outcomes were discounted at an annual rate of 3%. We conducted one-way and probabilistic sensitivity analyses to assess uncertainty. Results: In the base-case analysis without discounting, HepB-BD + HepB3 yielded a net cost saving of US18, 979 and saved 163 DALYs compared with HepB3 alone. With discounting, HepB-BD + HepB3 compared with HepB3 resulted in an incremental cost of US554 and 31 DALYs averted, translating into an ICER of US18/DALY averted. In one-way sensitivity analyses, HepB-BD + HepB3 remained cost-effective (at the cost-effectiveness threshold of US671 i.e. the Burkina Faso per-capita gross domestic product) for all parameter changes. However, results were very sensitive to variations in HepB-BD unit cost per vaccinated neonate and perinatal transmission risk in mothers carrying the hepatitis B e antigen. The probabilities of HepB-BD + HepB3 being cost-effective were 71.7% and 86.7%, at the cost-effectiveness thresholds of US335 and US671, respectively. Conclusion: Introducing HepB-BD in Burkina Faso is likely to be cost-effective.